Katere glasbene zvrsti najraje poslušajo predšolski otroci? - Habe, Katarina; Bratina, Tomaž (Revija za elementarno izobraževanje, 2018)
Which Music Genres are Prefered by Preschool Children? The aim of our study was to explore musical preferences in preschool children and also to shed light on parental influence. Quantitative study was conducted on 250 five- and six-year olds, 118 boys and 132 girls In the second part, we performed qualitative study on 15 children and their parents. Participants evaluated 10 one minute long musical excerpts and inqualitative study also reported reasons for (dis)liking. The results reveal that preschool children appreciate most of the musical styles, among which they like children song sung by a child the most. Parental influence was confirmed in qualitative part.DOI: 10.18690/1855-4431.11.1.77-90 (2018)COBISS-ID: 23816968
Keywords: musical preference; musical styles; preschool children; “open earedness”; parental influence